Diagnostic Value of Inflammatory Markers and Cytokines in Neonatal Sepsis - Lijie Wu (Evidence-Based Complementary and Alternative Medicine, 2022)
Objective. To explore the diagnosis value of inflammatory markers and cytokines in neonatal sepsis. Methods. In this retrospective analysis, 90 cases of neonatal sepsis admitted to our hospital from April 2019 to April 2021 were included in the observation group, and 70 healthy neonates who received routine physical examinations in our hospital during the same period were recruited as the control group. Comparison and analysis of inflammatory markers and cytokines levels between the two groups were performed on days 1, 3, and 7 after the onset. Flow cytometry was used to measure the white blood cells (WBCs) and percentage of neutrophils (N%), immunoturbidimetry was used to determine C-reactive protein (CRP), immunochromatographic analysis was used to determine procalcitonin (PCT) in plasma, and the enzyme-linked immunosorbent assay was used to determine interleukin-27 (IL-27), interleukin-6 (IL-6), interleukin-10 (IL-10), and tumor necrosis factor-α (TNF-α). Results. Compared with healthy controls, neonatal sepsis resulted in significantly higher levels of WBC, N%, PCT, and CRP on days 1, 3, and 7 after onset. The levels of WBC, N%, and PCT were continuously decreased from day 1 to day 7, while the levels of CRP were increased on day 1 and day 3 but declined on day 7 (P<0.05). Compared with healthy controls, patients with sepsis showed higher levels of IL-27, IL-6, IL-10, and TNF-α on days 1, 3, and 7 after the onset. The levels of IL-27, IL-6, and IL-10 were increased on day 1 and day 3 but decreased on day 7, and the levels of TNF-α were continuously decreased from day 1 to day 7 (all P<0.05). Conclusion. Neonatal sepsis was associated with fluctuating levels of WBC, N%, PCT, CRP, IL-27, IL-6, IL-10, and TNF-α at different time points of disease. The joint detection of the above indices provides a new pathway for the early diagnosis of neonatal sepsis.